The first electronic polytomous key to the world species of the subgenus Typhlodromus (Anthoseius) de Leon (Acari: Phytoseiidae) - Hernandes, Fabio Akashi [UNESP]; Kreiter, Serge; Tixier, Marie-Stéphane (Magnolia Press, 2012)
This paper describes the first polytomous computerised identification key within the family Phytoseiidae. It applies to the females of the world species of the subgenus Typhlodromus (Anthoseius) De Leon. This group is one of the largest within the family Phytoseiidae and the sub-family Typhlodrominae, with nearly 350 species currently recognised worldwide. No identification tool of these species exists at the world level, which makes their identification very difficult and unsecure. Thirty five characters were used to characterise each of the 343 species. Among these characters, 14 are discrete and 21 are continuous. The polytomous key was constructed using the free software DELTA 1.04 (DEscription Language for TAxonomy) and is freely available at the web site: http://www1.montpellier.inra.fr/CBGP/phytoseiidae/ anthoseiuskeypresentation. html. We hope that this work will open new perspectives for the identification of species of other genera (especially the largest ones, e.g. Neoseiulus, Euseius, Amblyseius) which contains more than 150 species and for which no key presently exists. We also expect that the present work will make the identification of the world species of Typhlodromus (Anthoseius) easier and more secure. Finally, we expect a contribution from the whole Phytoseiidae scientist community to improve subsequent versions of the key. Copyright © 2012 · Magnolia Press.
Keywords: Acari; Identification; Predators; Taxonomy